Comparison of creatinine‐based equations for estimating renal function for digoxin dose adjustment in patients with atrial fibrillation and heart failure. Issue 1 (10th January 2023) - Sakai, Masahiro; Hirai, Toshinori; Shitara, Satoshi; Iwamoto, Takuya; Shiga, Tsuyoshi
Abstract: The aim of this study was to determine an appropriate equation for estimating renal function to dose regulate the serum digoxin trough concentration to a target of <0.9 ng/ml in patients with atrial fibrillation (AF) and heart failure (HF). All patients received 0.125 mg oral digoxin daily. The estimated glomerular filtration rate by the Modification of Diet in Renal Disease (eGFRMDRD ) equation deindexed based on body surface area had the highest correlation with digoxin trough concentrations ( r = −0.450) compared to the Cockcroft‐Gault equation ( r = −0.415) or deindexed eGFR based on the Chronic Kidney Disease Epidemiology Collaboration (eGFRCKD‐EPI ) equation ( r = −0.416). The median digoxin trough concentrations were 0.60, 0.77, 0.97 and 1.30 ng/ml in patients with a deindexed eGFRMDRD ≥ 60, 45–59, 30–44 and < 30 ml/min, respectively. The deindexed eGFRMDRD is an appropriate equation for digoxin dose adjustment in patients with AF and HF. Abstract : The estimated glomerular filtration rate by the Modification of Diet in Renal Disease (eGFRMDRD ) equation deindexed based on body surface area had the highest correlation with digoxin trough concentrations ( r = −0.450) compared to the Cockcroft‐Gault ( r = −0.415) or deindexed eGFR based on the Chronic Kidney Disease Epidemiology Collaboration (eGFRCKD‐EPI ) equation ( r = −0.416).